Determinants of gender based wage discrimination of agriculture wage laborer in Bangladesh - Rahman, Wakilur (Bangladesh Agricultural University, 2019)
Presented by Wakilur Rahman (Bangladesh Agricultural University), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.